Navigating the landscape of legal medicine: a 4-year analysis of forensic consultations in an Italian hospital - Visci, Paolo; Sirago, Gianmarco; Vinci, Annachiara; Calò, Francesco; De Micco, Francesco; Benevento, Marcello; Solarino, Biagio; Dell’Erba, Alessandro; Ferorelli, Davide (Frontiers in Medicine, 2025)
IntroductionThis study explores a comprehensive 4-year retrospective analysis of 511 forensic consultations conducted at “Policlinico” hospital in Bari, Italy. It highlights the expanding role of legal medicine within healthcare settings, an area that has traditionally been limited to expert testimony and forensic pathology. Over time, legal medicine in Italy has evolved to address a variety of clinical areas, including informed consent, disability assessment, personal injuries, and sexual violence. This research aims to examine these diverse applications and their impact on patient care.MethodsData were systematically categorized and analyzed using a multivariate multinomial regression model. The study focused on key variables, such as patient demographics and timing of shifts, to identify significant determinants that influence the types of forensic consultations conducted. The dataset consisted of 511 consultations, covering a range of clinical and legal issues.ResultsThe analysis revealed that informed consent issues were the most prominent, with 58.7% of consultations addressing concerns related to patient autonomy and the capacity for consent, particularly in neuropsychiatric conditions. Personal injury consultations accounted for 24.3% of the total, and sexual assault cases made up 10%. These results underscore the intersection of medical practice and forensic evaluation, highlighting societal issues such as interpersonal violence and the importance of legal medicine in healthcare.DiscussionThe findings highlight significant gaps in the literature regarding the broader applications of legal medicine, especially in terms of integrating advanced methodologies like artificial intelligence. Such technologies could enhance patient profiling and predictive care, ultimately improving patient safety, risk management, and the protection of patient rights. The study advocates for structured forensic consultation services to be incorporated into clinical practice, emphasizing the role of legal medicine in improving patient-centered care and promoting justice. These insights are crucial for healthcare professionals, administrators, and policymakers aiming to optimize healthcare systems.